Effect of cisplatin on pancreas and testies in Wistar rats: biochemical parameters and histology - Yadav, Yogesh Chand (Heliyon, 2019)
OBJECTIVE: To investigate effect of cisplatin on biochemical parameter and histology of pancreas and testis in Wistar rats. MATERIAL AND METHODS: Single dose cisplatin (10 mg/kg) was injected by intraperitoneal route in Wistar rats. Blood was withdrawn on 7(th) day from cisplatin treated rats by retro-orbital sinus for biochemical estimation. Further rats were scarified and dissected out their pancreases and testes for estimation of antioxidant enzymes and histopathological study. RESULTS: The cisplatin-treated group showed a significantly (P < 0.01) increased blood glucose level, Glycosylated hemoglobin in blood on the 7(th) day as compared to the control group. Whereas cisplatin-treated group showed significantly (p < 0.001) increased lipid peroxidation and decreased reduced glutathione, superoxide dismutase, catalase in pancreatic and testicular tissue as compared to the control group. Histopathological sections of the pancreatic tissue showed marked vasoconstriction and micro infiltration were observed however testicular tissue showed degeneration in some somniferous tubules and also greatly depleted of germ cells in cisplatin treated group. CONCLUSION: These findings demonstrated that the cisplatin could be induced diabetes and testicular toxicity due to their free radical mediated oxidative stress.